The Influence of Leadership, Human Resource Development, Job Satisfaction on the Performance of Employees at the Ministry of Religion of Lahat Regency - Alviona Alviona; Nisma Aprini; Darmin Darmin (Utami Publisher, 2026)
The purpose of this study is to determine and analyze the influence of leadership, human resource development, and job satisfaction, individually and collectively, on the performance of employees at the Ministry of Religious Affairs Office in Lahat Regency. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial and simultaneous tests, and the coefficient of determination. The results showed that leadership significantly influenced the performance of employees at the Ministry of Religious Affairs Office in Lahat Regency. Human resource development significantly influenced the performance of employees at the Ministry of Religious Affairs Office in Lahat Regency. Job satisfaction significantly influenced the performance of employees at the Ministry of Religious Affairs Office in Lahat Regency. Leadership, human resource development, and job satisfaction simultaneously significantly influenced the performance of employees at the Ministry of Religious Affairs Office in Lahat Regency.